1951
DOI: 10.1161/01.cir.4.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Observations with Radioactive Hydrogen (H 3 ) in Experimental Atherosclerosis

Abstract: Tritium has been used to study certain aspects of endogenous and exogenous cholesterol metabolism in normal and hypercholesterolemic rabbits. Special attention is given to turnover studies on aortic cholesterol. Labeled cholesterol has been used for feeding experiments an(l the subsequent rise of serum cholesterol specific activity has been investigated.G OFMAN and co-workers' have made observations on the mode of transport of cholesterol in lipoprotein molecules in serum, and have presented evidence to link t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1952
1952
2008
2008

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…These results are in agreement with the findings of Spritz, Ahrens, and Grundy (15) (19). The turnover time in the present studies for rabbit serum cholesterol was longer (average 25.4 days) than has previously been reported (30). This difference is probably due to the fact that our studies were carried out over a very long period of time in order to be certain that the specific activity declined at an exponential rate.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the findings of Spritz, Ahrens, and Grundy (15) (19). The turnover time in the present studies for rabbit serum cholesterol was longer (average 25.4 days) than has previously been reported (30). This difference is probably due to the fact that our studies were carried out over a very long period of time in order to be certain that the specific activity declined at an exponential rate.…”
Section: Discussionsupporting
confidence: 93%
“…However, qualitative changes occur in the blood cholesterol, since as has been shown by Biggs et al (12), ingested labelled cholesterol quickly interchanges with blood cholesterol. More recently also, Page et al (26), have demonstrated that the lipoproteins of intestinal lymph change following ingestion of cholesterol and with the drainage of such lipoproteins into the blood stream it seems most likely that for a while at least, the plasma cholesterol is altered qualitatively.…”
Section: Discussionmentioning
confidence: 81%
“…The non-saponifiable material was extracted with ether. The cholesterol was precipitated with digitonin and the specific activity determined as described previously (9,10).…”
mentioning
confidence: 99%